Custos e benefícios da Lei Sarbanes-oxley o caso de uma empresa automobilística - Milleo, Delmo (2008)
This scientific study main purpose is evaluate the costs and benefits impacts recognized by the high level administration inside an automobilist industry after the organizational controls adoption required by the SOX law (Sarbanes-Oxley). The accounting concepts were reviewed and discussed as well as costs and organizational controls, controls mechanisms, corporative governance foreseen by COSO (Committee of Sponsoring Organization of the Tread way Commission), internal control and the SOX law. The financial scandals occurred in the North American stock market in 2002 motivated a special necessity to focus on transparence related to internal controls processes, encouraging North American congress to promulgate SOX law. Any company with trade on North American stock options is obliged to follow new rules in all subsidiaries in any country of the world. Volvo do Brazil company is one these companies and were chosen to apply this scientific study because Volvo adopted all SOX requirements and quitted North American stock options two years later. The methodology used is a case study with a pre-defined script and questions half-structuralized. Author tried to identify which are all recognized costs and benefits by the high level administration after the law implementation at the company. The conclusion was that at certain level of bureaucracy the internal controls implementation generates recognized benefits by the high level administration adding value to the process. On the other hands when exceeded the bureaucracy it can make impossible certain processes if we consider costs overcoming benefits. After left North American stock options Volvo decided remain all controls implemented since they are enough to trade at the European market.